Case Report: Niraparib-Related Pulmonary Embolism During the Treatment of BRCA Mutant Advanced Ovarian Cancer - Wei, Qiang; Chen, Dong-Sheng; Liu, Yuan-Hua (Frontiers in Oncology, 2022)
Niraparib, an oral, potent, highly selective poly (ADP-ribose) polymerase (PARP) inhibitor, has promising clinical benefit for maintenance treatment of patients with ovarian cancer in partial response to platinum-based chemotherapy, especially in patients with BRCA mutation. In publicly available niraparib-related treatment adverse events, gastrointestinal disorders and haematological toxicities were most commonly reported with manageable safety profile. Herein, we firstly describe a severe and never reported pulmonary embolism (PE) associated with the use of niraparib in a patient with BRCA mutation advanced high-grade serous ovarian cancer, and received anticoagulant therapy after PE. There have been no reports of PE caused by the use of niraparib in patients with advanced high-grade serous ovarian cancer, knowledge of the occurrence of PE after the use of niraparib may assist other clinicians in managing this rare but potentially serious toxic effect.